2021
DOI: 10.1177/00031348211047507
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Injuries in Manual and Mechanical Cardiopulmonary Resuscitation

Abstract: Purpose Mechanical chest compression has been shown to be equivalent to manual chest compression in providing survival benefits to patients experiencing cardiac arrest. There has been a growing need for a contemporary review of iatrogenic injuries caused by mechanical in comparison with manual chest compression. Our study aims to analyze the studies that document significant life-threatening iatrogenic injuries caused by mechanical and manual chest compression. Methods A systematic review of PubMed and Embase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Mechanical chest compression devices have been associated with elevated injury rates, including rib fractures, but also with improved 30-day survival for in-hospital cardiac arrest. 9 , 11 , 25 , 26 , 27 On the other hand, no study has shown a clear benefit of mechanical CPR for out-of-hospital cardiac arrest (OHCA). 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Mechanical chest compression devices have been associated with elevated injury rates, including rib fractures, but also with improved 30-day survival for in-hospital cardiac arrest. 9 , 11 , 25 , 26 , 27 On the other hand, no study has shown a clear benefit of mechanical CPR for out-of-hospital cardiac arrest (OHCA). 28 , 29 …”
Section: Discussionmentioning
confidence: 99%
“…Mechanical chest compression has been reported to be associated with a higher risk of injuries than manual chest compression, particularly life‐threatening visceral injuries, with a study showing a prevalence of 10.7% potentially life‐threatening injuries in cases receiving mechanical chest compression, compared with none in the manual chest compression cases [1]. Iatrogenic injuries from chest compression most commonly involve rib fractures, sternal fractures, and lung injuries [2]. Liver injuries are infrequent, ranging from an incidence rate of 0.3% [1] to 3% [3] in various studies.…”
Section: Introductionmentioning
confidence: 99%